Peripartum anesthetic management of patients with inflammatory bowel disease, a retrospective case-control study - Andres Freundlich; Eytan Gozal; Sorina Grisaru-Granovsky; Ariel Grass; Ariella Bar-Gil Shitrit; Alexander Ioscovich (Elsevier, 2021)
Objective: Inflammatory bowel diseases (IBD) are a group of pathologies associated with an increased rate of abortions, premature deliveries, cesarean sections and other morbidity during the peripartum period. The objective of this retrospective study was to investigate the anesthetic management for delivery of women with IBD. Material and methods: The records of patients with IBD, who delivered at our Center, were obtained for data which included anesthetic and obstetric management as well as neonatal outcome. Five subgroups were defined based on mode of delivery, presence or absence of epidural in normal vaginal delivery (NVD) and urgency of cesarean section, each of which was compared with control groups of healthy parturients in the same period. Additionally, the rate of cesarean sections and the use of epidural analgesia for NVD were compared with the general obstetric population of our center in the same period. Results: 107 patients with IBD who delivered at our center were studied. The rates of cesarean sections and emergency cesarean sections were significantly higher compared to the general population. However, the rate of instrumental delivery and of epidural analgesia use for NVD were similar. Among those who underwent cesarean sections, no significant differences were found in anesthesia type, surgery duration, number of complications, type of monitoring or postoperative management compared to the control group. Conclusion: Peripartum anesthetic management of patients with IBD does not differ significantly from that of parturients without it. Anesthesiologists can plan their anesthesia in a similar way as they do in healthy parturients.